Pembentukan Customer Loyalty Restoran: Peran Gastronomy Experience, Service Quality, dan Customer Satisfaction - Kathleen Alexandra; Jessica Felicia Soesanto; Adrie Oktavio (LPPM Universitas KH A. Wahab Hasbullah, 2026)
The escalation of growth in the culinary industry in the Surabaya region has triggered a significant intensity of competition, making customer retention a crucial issue, especially in the gastronomic restaurant sector. This study is oriented toward examining the impact of gastronomy experience, service quality, and customer satisfaction on customer loyalty. Through a quantitative approach, a purposive sampling technique was applied to involve 180 participants as the research sample. Data collection was conducted using a 5-point Likert scale questionnaire, which was then analyzed using the PLS-SEM method. The research findings demonstrate that customer satisfaction is positively and significantly influenced by gastronomy experience and service quality. In the context of this study, service quality has a stronger influence compared to gastronomy experience. Furthermore, a positive and significant effect was also found in the relationship between customer satisfaction and customer loyalty. The conclusion of this study emphasizes that, based on the perspective of Stimulus-Organism-Response (SOR) Theory in the gastronomic restaurant ecosystem, the formation of customer loyalty is projected to be more dominantly driven through the stimulation of service quality and the perception of customer satisfaction.